The Radical Republicans and Reform in New York during Reconstruction - Mohr, James C. (Cornell University Press, 2019)
New insights into the politics of the Reconstruction era are offered in this study. Contending that the North, as well as the South, underwent reconstruction after the Civil War, the author examines the kinds of legislation the Radical Republicans tried to enact when they gained control in New York. Reform is the central theme of the book: fire protection, public health, labor, education, and voting are some of the areas covered. White reaction to black suffrage, the author maintains, brought dissension to, and meant defeat for, a political coalition that had begun to launch a reform program with profound implications.